Clypeaster scillae Desmoulins, 1837 from Miocene beds near Podgračeno, Eastern Slovenia - Mikuž, Vasja (Geologija, 1998)
In the paper, an irregular sea urchin from Podgračeno is considered. The locality-occurs in Badenian beds that consist of lumachelles of large ostreas, lithothamnian limestone and biocalcarenite. Next to ostreas appear also other bivalve species, gastropods, barnacles and sea urchins. The fossil belongs to species Clypeaster scillae Desmoulins, 1837, that is relatively rare in Slovenia, found only in a few localities. According to literature, the species is frequent in Lower and Middle Miocene beds of Tethys, and in Badenian beds of Paratethys.